Review of Dashavidha Pariksha and Its Practical Applicability in Ayurveda - Dr. Swati Pandit Sarnaik, Dr. Jijaba M. Shirke, Dr. Ranjit Anil Deshmukh, Dr. U. J. Shirke (Drugs and Cell Therapies in Hematology, 2021)
Indian traditional medicine; ayurveda has a great history. Diagnosis according to ayurveda is not merely naming the disease but identification of imbalance of trienergies doshas. The patient is the true element of examination. The examination of Patient is conducted for knowledge of strength, life span of the patient and strength of vitiate doshas. In ayurveda disease diagnosis process (pariksha) means viewing or examining from all sides and aspects. The aim of pariksha is “ Pratipattigyanam” means proper knowledge and this pariksha is broadly classified into two method which are Rogi pariksha and Rog pariksha and these is the complete protocol of comprehensive clinical examination On primary level patient should be examine through inspection, palpation and interrogation. According to ancient science patient also examine through dashavidh pariksha which comes under the rogi pariksha. Dashavidh pariksha includes examination of Prakruti, vikruti, saar, sanhanan, praman, satmya, satva, ahar shakti, vyayam shakti and vaya. This ten aspects should be examined to assess the strength of diseases and individual. Among these dashavidh pariksha except vikruti pariksha is to be done to understand the overview condition of person. Vikruti pariksha is to be done to elicit the factors which are responsible for the pathogenesis of the diseases. In present article, review of dashavidha pariksha is very essential because before planning any treatment one should have complete knowledge of roga bala and rogibala.